Investor response to the implementation of IFRS 9 in Indonesian banking companies - Firmansyah, Amrie; Kurniawati, Lestari; Miftah, Desrir; Winarto, Tjahjo (Jurnal Akuntansi dan Auditing Indonesia, 2023)
This study examines the effect of allowance for impairment losses on firm value. Allowance for impairment losses on the company's financial assets in the context of implementing IFRS 9 in the form of PSAK 71 in Indonesia on a forward-looking basis is different from the implementation of previous accounting standards, which was on a backward-looking basis. Quantitative methods are employed in this study using secondary data from banking financial reports sourced from www.idx.co.id during the 2019-2021 period. In addition, this study also employs stock price data sourced from www.finance.yahoo.co.id. The main data in this study is data for 2020, which is the first year of application of PSAK 71. While data for 2019 is used to compare the year before the application of PSAK 71, and 2021 is used to compare the application of PSAK 71 in the second year. Data testing was performed using multiple linear regression analysis for cross-section data. This study concludes that the allowance for impairment losses positively affects firm value in the first year. The results of this test are relevant in the second year of the implementation of PSAK 71. Meanwhile, it shows that the allowance for impairment losses has no effect on firm value in the year before the implementation of PSAK 71. This research contributes to the literature on implementing new financial accounting standards in Indonesia related to investor response in the capital market.